Laparoscopic pancreatectomy: Did the indications change? A review from literature. (September 2015) - Sperlongano, P.; Esposito, E.; Esposito, A.; Clarizia, G.; Moccia, G.; Malinconico, F.A.; Foroni, F.; Manfredi, C.; Sperlongano, S.; Gubitosi, A.
Abstract: Pancreatic Cancer (PC) is the fourth cause of death for tumors in Western countries. Symptoms are not specific, and can vary according to the tumor size and place. Diagnostic workup includes CA 19-9, CT and MRI. Surgery is the only treatment for PC, associated to radio-chemo therapy. Laparoscopic approaches are actually used for PC treatment in few specialized centers, and could be an alternative to laparotomic surgery. The aim of our study is to evaluate the efficacy of laparoscopy for PC treatment compared to laparotomy. We reviewed 19 articles in literature to assess the feasibility and efficacy of Laparoscopic Distal Pancreatectomy (LDP) and Laparoscopic Pancreaticoduodenectomy (LPD). The results have shown that LDP is nowadays a safe technique, and the outcomes are comparable to laparotomic surgery. Regarding to LPD instead, results are controversial and the data are still not sufficient to consider this technique as a valid alternative to laparotomic surgery.